Analisis Prinsip Keadilan Dalam Konteks Pembiayaan Mudharabah Pada Bank Pembiayaan Rakyat Syariah Al- Washliyah Medan - Nurhamizah Hutagalung (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is field (field research) at PT BPRS Al Washliyah Medan. Peoples financing Bank Medan. Financial institutions in general are companies engaged in financi, raisng funds, distributing funds or both. One form of financials in institutions is the bank. Bank is a business entity that collects funds from the public in the form of savings and distributes them to the community in the form of credit and/or other form in the order to improve the peoples standard of living. The formulation on the problem studied is how the theoritical concept of the principle of justice in the context of the mudharabah contract and how the application of the principle of justice in the context of financing the mudharabaah contract at BPRS Al Washliyah Medan.Mudarabah financing product at PT. The Islamic People's Financing Bank Al Washliyah is very helpful and encourages banks to provide Mudharabah financing to the community. However, not a few customers who do not meet the requirements to perform the mudharbah contract and lack of honesty with customers in terms of business development. The Islamic People's Financing Bank Al Washliyah Medan has not been maximized in the fairness of the mudharabah financing contract. Keywords: Justice, Financing, and Mudharabah